Proyecto de pre-factibilidad para la producción y comercialización de Persianas Zebra en la empresa Uditex de la ciudad de Loja. - Uyaguari Romero, Luis Ronaldo (2022)
The aim of this research is to determine the pre-feasibility for the production and commercialization of zebra blinds in the company Uditex in the city of Loja. This research applied a simple descriptive technique like interviews, surveys, and direct observation, which helped to determine a sample that allowed segmenting the population to be research. Thus, a total of 384 surveys were applied to Loja families of middle, upper-middle and high social status, where the results determined the unsatisfied demand of 11,553 square meters of the most representative blinds, finally the marketing plan of the company was established to compete in the market. The capacity utilized will be 10,080 square meters of blinds per year and a market share of 87.43% during the first year. It was determined that an investment of $32,260.41 dollars is required to start up the production plant. Through the cost analysis, the retail price was determined, resulting in a market price of $24.50 per square meter. Regarding the financial indicators such as the Net Present Value (NPV) obtained a positive result of 34,728.73, while the Internal Rate of Return (IRR) was 56.99%, the Cost-Benfit Ratio (RBC) obtained 0.24 cents for each dollar invested. The Capital Recovery Period (CRP) capital will be recovered in 2 years, 8 months and 15 days, and finally, the sensitivity analysis with the maximum percentage increase in costs is 1.20%, and the maximum decrease in income is 1.04%. Therefore, the project is not sensitive to these variations that can influence its profitability. Finally, it is concluded that this investment project has been determined to be feasible for its execution according to its financial indicators and its implementation is recommended since it is expected to obtain profitability and economic benefits as soon as the operational phase begins.